Balancing Cost and Specifications: In high precision optical manufacturing small changes can have a large impact on cost. Issue 2 (14th April 2018) - Adams, Daniel
Abstract: When specifying an optic, even something as simple as a single spherical lens, it is very important to have a clear understanding of what each specification is and how it could affect your system. At high precision, there is usually a cost‐benefit trade‐off and the goal should be to try to optimize that. This article will look at the key specifications in a spherical lens system and explore the cost‐benefit considerations when working at high levels of precision.